Penerapan Model Pembelajaran Cooperative Learning Tipe STAD (Student Team Achievement Division) untuk Meningkatkan Hasil Belajar Sejarah Peserta Didik di kelas X-5 di SMA Negeri 3 Medan - Sinurat, Lulu Luciana (ALACRITY : Journal of Education, 2024)
This research is classroom action research which aims to improve or improve history learning practices that have previously been carried out in the classroom through the application of the STAD (Student Team Achievement Division) type cooperative learning model to improve history learning outcomes. The subjects of this research were students in class X-5 at SMA Negeri 3 Medan with a total of 36 students. The indicators examined in this research are students' history learning outcomes. Based on the pre-cycle results, it is known that student learning completion reached 47.2% with 17 students completing the study with an average score of 61.94. After using the STAD cooperative learning model in cycle I, student learning completion reached 72.2% with 26 students completing and the average student score was 72.36. Based on the research results, it is known that student learning mastery has increased, but has not yet met the research success indicator, namely 75%, therefore a cycle II is needed. The results of research in cycle II showed that the class average reached 85.13 and the completion rate reached 83.3% with 30 students completing. The results of the second cycle of research have met the research success indicators, namely the score obtained is more than ? 80 with a learning completeness level reaching ? 75%. So it can be concluded that learning history using the Cooperative Learning STAD technique learning model can improve student history learning outcomes in class X-5 SMA Negeri 3 Medan.